Малоизвестные полужесткокрылые (Heteroptera) юга СССР - Пучков, В.Г.; Пучков, П.В. (Вестник зоологии, 1983)
Brief habitat characteristics and food relations data for 20 Heteropteran species. Redescription of Plagiorrhamma concolor Reut, Phytocoris moestus Reut, Lopidodenus ogivus Putsh., bona sp., Chlamydatus evanescens (Boh) and Hyalochilus dolosus Horv.